Polymerase Chain Reaction Analysis of Pork DNA in Unauthorized Jamu and Fish Oil Capsule Shells - Asra, Ridho; Fauziah, Fitra; Sarina, Gemmy; Hasan, Rahmi Zhavira; Yahya, Ghina Muharrani (Asian Journal of Pharmaceutical Research and Development, 2022)
Capsules for pharmaceutical dosage forms are generally manufactured from beef gelatin. However, several reports claimed the alleged misuse of pork gelatin was improperly used in producing illegitimate capsules for the Muslim community. This study aimed to analyze pork DNA in unregistered jamu and fish oil capsules using the Polymerase Chain Reaction (PCR) method. The sample was isolated to obtain pure pork DNA and amplified using a specific primer to generate millions of DNA using the multi-step PCR method. The PCR product was analyzed to identify the pork DNA's existence via gel electrophoresis in 1.5% agarose. The analysis showed that several samples were positive at 132 bp compared to reference pork DNA. The result of this study revealed that unregistered products should be evaluated and followed up on to prevent product abuse.